The iNKT cell ligand α-GalCer prevents murine septic shock by inducing IL10-producing iNKT and B cells - Park, Yun Hoo; Lee, Sung Won; Kim, Tae-Cheol; Park, Hyun Jung; Van Kaer, Luc; Hong, Seokmann (Frontiers in Immunology, 2024)
Introduction: α-galactosylceramide (α-GalCer), a prototypical agonist of invariant natural killer T (iNKT) cells, stimulates iNKT cells to produce various cytokines such as IFNγ and IL4. Moreover, repeated α-GalCer treatment can cause protective or pathogenic outcomes in various immune-mediated diseases. However, the precise role of α-GalCer-activated iNKT cells in sepsis development remains unclear. To address this issue, we employed a lipopolysaccharide (LPS)/D-galactosamine (D-GalN)-induced murine sepsis model and two alternative models. Methods: Sepsis was induced in wild-type (WT) C57BL/6 (B6) mice by three methods (LPS/D-GalN, α-GalCer/D-GalN, and cecal slurry), and these mice were monitored for survival rates. WT B6 mice were intraperitoneally injected with α-GalCer or OCH (an IL4-biased α-GalCer analog) one week prior to the induction of sepsis. To investigate the effects of α-GalCer-mediated iNKT cell activation on sepsis development, immune responses were analyzed by flow cytometry using splenocytes and liver-infiltrating leukocytes. In addition, a STAT6 inhibitor (AS1517499) and an IL10 inhibitor (AS101) were employed to evaluate the involvement of IL4 or IL10 signaling. Furthermore, we performed B cell adoptive transfers to examine the contribution of α-GalCer-induced regulatory B (Breg) cell populations in sepsis protection. Results: In vivo α-GalCer pretreatment polarized iNKT cells towards IL4- and IL10-producing phenotypes, significantly attenuating LPS/D-GalN-induced septic lethality in WT B6 mice. Furthermore, α-GalCer pretreatment reduced the infiltration of immune cells to the liver and attenuated pro-inflammatory cytokine production. Treatment with a STAT6 inhibitor was unable to modulate disease progression, indicating that IL4 signaling did not significantly affect iNKT cell-mediated protection against sepsis. This finding was confirmed by pretreatment with OCH, which did not alter sepsis outcomes. However, interestingly, prophylactic effects of α-GalCer on sepsis were significantly suppressed by treatment with an IL10 antagonist, suggesting induction of IL10-dependent anti-inflammatory responses. In addition to IL10-producing iNKT cells, IL10-producing B cell populations were significantly increased after α-GalCer pretreatment. Conclusions: Overall, our results identify α-GalCer-mediated induction of IL10 by iNKT and B cells as a promising option for controlling the pathogenesis of postoperative sepsis.